A token-based investigation of verbal plurality in Lithuanian dialects - Kozhanov, Kirill; Wiemer, Björn (Kalbotyra, 2019)
This paper examines the use of the verbal suffixes -(d)inė- and ‑dav‑ in Lithuanian dialects. Both suffixes express pluractionality, although of different types, and their distribution in Lithuanian dialects differs as well. Using corpus data, we find that in South Aukštaitian ‑dav‑ is rarer and -(d)inė‑ is more frequent than in East Aukštaitian; in Lithuanian dialects of Belarus -dav- is almost absent. We argue against the assumption that -(d)inėforms have extended into the domain of the past habitual at the expense of ‑dav‑ forms; a slightly higher token frequency of -(d)inė‑ in South Aukštaitian seems to apply irrespective of any particular tense. We also argue that only token-based analyses can substantiate claims concerning areal distribution of certain grammatical forms and constructions.